Organic Acid Exposure Enhances Virulence in Some Listeria monocytogenes Strains Using the Galleria mellonella Infection Model - Li, Minghao; Carpenter, Charles E.; Broadbent, Jeff R. (Frontiers in Microbiology, 2021)
Prior research has suggested that the use of organic acids in the food industry may unintentionally enhance pathogenicity of Listeria monocytogenes strain N1-227 and R2-499. This study explored the connection between habituation to L-lactic acid or acetic acid and virulence in L. monocytogenes strains N1-227 and R2-499 using selected gene expression analysis and the in vivo Galleria mellonella wax worm model for infection. Expression of transcription factors (sigB and prfA) and genes related to acid resistance (gadD2, gadD3, and arcA) and bile resistance (bsh and bilE) or to virulence (inlA, inlB, hly, plcA, plcB, uhpT, and actA) was investigated by quantitative real-time PCR (qRT-PCR), while in vivo virulence was assessed by following the lethal time to 50% population mortality (LT50) of G. mellonella larvae after injection of untreated and habituated L. monocytogenes. Twenty minutes of habituation to the organic acids at pH 6.0 significantly increased expression of key acid and bile stress response genes in both strains, while expression of virulence genes was strain-dependent. The expression of transcription factor sigB was strain-dependent and there was no significant change in the expression of transcription factor prfA in both strains. Habituation to acid increased virulence of both strains as evidenced by decreased LT50 of G. mellonella larvae injected with Listeria habituated to either acid. In summary, habituation of both L. monocytogenes strains to organic acids up-regulated expression of several stress and virulence genes and concurrently increased virulence as measured using the G. mellonella model.